Role of attitude towards divorce in relationship between family factors and romantic relationship quality among university and college students in the Maldives - Sanoora, Aishath (2021)
Family factors such as interparental conflict, parental divorce, and parent-child attachment have often been associated with young adults' romantic relationship quality. Research has also shown that these factors are interrelated; however, little attention has been given to look at all the elements together in a single study. In line with this, the current study has aimed to examine the impact of interparental conflict, parental divorce, and parent-child attachment on the relationship quality of young adults in Maldives' universities and colleges. The study also examined the mediation effect of attitudes towards divorce on the relationship between interparental conflict, parental divorce, parent-child attachment and romantic relationship quality. A total of 463 Maldivian university/college students in a romantic relationship (i.e., either married or in a dating romantic relationship) between the ages of 18 to 25 participated in the study. Data were collected using self-administered questionnaires. Relationship quality was measured using relationship quality component inventory. Children's perception of interparental conflict scale was used to measure interparental conflict. The parent-child attachment was measured using an attachment to parent/caregiver inventory, and attitudes towards divorce were measured using the attitudes towards divorce scale. The collected data was analyzed using SPSS v.26 and Smart-PLS 3 software. The descriptive analysis results showed a higher percentage of the participants had low relationship quality levels, perceived high levels of interparental conflict, and had experienced parental divorce. Furthermore, mother-child avoidant attachment was slightly higher than the father-child avoidant attachment. However, mother-child anxious attachment was higher among the participants than a father-child anxious attachment. Additionally, most participants had unfavorable attitudes towards divorce, meaning they accepted divorce as an easy way to terminate complicated relationships. PLS-SEM results showed a direct relationship between interparental conflict, parental divorce, parent-child attachment, attitude towards divorce, and romantic relationship quality. The results also showed that the attitude towards divorce mediated parental divorce and romantic relationship quality. However, there was no mediating effect of attitude towards divorce on the relationship between interparental conflict and romantic relationship quality. Interparental conflict, parental divorce, parent-child attachment, and attitude towards divorce contributed (69.0 %) to the quality of the romantic relationship of the young adults. The main predictor of romantic relationship quality was found to be interparental conflict. It is important for relevant authorities to come up with relevant awareness and interventions programs for parents on how to manage their conflict. Furthermore, parental divorce, attitude towards divorce, and parent-child attachments also need attention as they are contributing factors to romantic relationship quality among young adults of Maldives. However, other factors contribute to the quality of the romantic relationship, that need to be studied in future research.